Sufficient number of experiments for the adaptability and stability analyses of maize using the Eberhart and Russell method - Cargnelutti Filho, Alberto; Guadagnin, José Paulo (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to determine the sufficient number of experiments (environments) for the adaptability and stability analyses of maize cultivars, using the Eberhart and Russell method. Grain yield data from 63 trials of maize cultivars from six groups of experiments were used. In each group, new data files were formed from all experiments (n), for the combinations of 3, 4, ..., n-1 experiments, totaling 10,381 files. Mean and estimates of the adaptability (b) and stability (S2d) parameters were obtained for each cultivar, in each file. A power function was adjusted for the amplitudes of b and S2d (dependent variables) in each cultivar, as a function of the number of experiments (independent variable), totaling 290 equations (145 cultivars × two dependent variables). For each equation, the value was determined on the abscissa axis (Xs, sufficient number of experiments), corresponding to the point of maximum curvature. The highest value among the 290 estimates of Xs, rounded up to the nearest integer, was assumed to be the sufficient number of experiments for the analyses. Seven experiments are sufficient to analyze the adaptability and stability of maize cultivars using the Eberhart and Russell method.